Construção e validação de protocolo da CIPE® para a prevenção e tratamento da pessoa com lesão por pressão - Oliveira, Danielle Martins do Nascimento (2020)
Introduction: Pressure injuries are considered a public health problem, due to their high incidence. Objective: To validate a CIPE® Protocol built for the prevention and treatment of people with pressure injuries in the light of the theoretical model of Horta. Method: It was a qualitative and quantitative methodological research, carried out in the following stages: 1) integrative review and mapping of terms with ICNP® 2017, 2) content validation of nursing interventions with specialist nurses, 3) preparation of the flowchart for using the protocol, and 4) structuring of the ICNP® protocol for the prevention and treatment of pressure injuries. From the first stage, 31 articles were extracted, and 74 nursing interventions were identified. These interventions were mapped with CIPE 2017 and classified as equal, similar, more comprehensive, more restricted and there is no agreement. The instrument was structured and sent to perform content validation by 30 specialist nurses, in order to assess whether or not they were applicable to the prevention and treatment of people with pressure injuries. Data collection took place from November 2018 to May 2019. Data analysis was performed using the statistical package R. The interventions considered applicable were those that reached the Content Validity Index greater than or equal to 0.80 in the validation, p-value less than or equal to 0.05 and Cronbach's alpha above 0.80. This study, before being started, was assessed by CEP / HULW / UFPB and approved by CAAE 96366318.8.0000.5183, under opinion no. 2,965,744. Results: It was evidenced with the statistical analysis that 93.67% of the statements of nursing interventions had a Content Validation Index greater than 80%, the p-value for the proportion equality test was less than 0.05 and high levels of Cronbach's alpha. Five 6.33% interventions had a Content Validity Index below 80%, therefore, they were removed from the instrument. A care flow chart was elaborated and the protocol was structured with 74 nursing interventions considered applicable in the prevention and treatment of people with pressure injuries. Conclusion: The findings of this study will strengthen clinical practice, teaching and the scientific community in the prevention and treatment of people with pressure injuries.